Influencing factors, evolution, and strategies for improving the quality of traditional Chinese medicine patents: an empirical study based on patent invalidation cases - Li, Xin (Annals of medicine (Helsinki), 2024)
This study analyzes 134 invalidated traditional Chinese medicine (TCM) patents from 1984 to 2021 to explore common weaknesses and track quality progression. The findings highlight that TCM patents applied for between 2001 and 2005 face higher invalidation rates, with disputes often arising 4-7 years post-application. Disputes are concentrated in patents related to cardiovascular and cerebrovascular diseases, exacerbated by widespread geographical distribution and technology saturation. Combination patents are more prone to invalidation than single-component ones, and patents using preparation methods to describe products carry hidden risks. Additionally, citing more references positively impacts patent stability. Despite progress, TCM patents still encounter significant challenges in quality and consistency.